Alloy film on the surface of wind power metal component and its processing method and application
Through ultrasonic shot peening, alternating sputtering and segmented gradient heat treatment technology, a multi-layer film of the surface of wind power metal components was prepared, solving the problem of insufficient environmental corrosion resistance, wear resistance and deformation resistance in harsh environments. Achieve significant performance improvement and service life extension.
Patent Information
- Application Number
- CN202411371714.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2044-09-29
AI Technical Summary
Wind power metal components face problems such as insufficient resistance to environmental corrosion, wear and deformation resistance in harsh environments, resulting in shorter service life and increased safety risks.
Through synergistic action of ultrasonic shot peening, alternating sputtering and segmented gradient heat treatment, a TaNbW/TiVCr multilayer film combined with metallurgy diffusion on the surface of wind power metal components was prepared to form a surface alloy film with high hardness, strong wear resistance and environmental corrosion resistance.
It significantly improves the environmental corrosion resistance, wear and deformation resistance of wind power metal components, extends service life and reduces safety risks.
Smart Images

Figure CN118880242B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an alloy film on the surface of a wind power metal component and a processing method and application thereof, belonging to the technical field of material surface treatment. Background Art
[0002] Wind power metal components, as the core components of wind power generation systems, carry the important mission of converting wind energy into electrical energy. These components not only need to have extremely high wear resistance and deformation resistance to cope with the challenges of harsh natural environments, but also need to have excellent corrosion resistance to ensure stable performance during long-term operation. In wind power equipment, there are many types of metal components with different functions. For example, the tower and main shaft of the wind turbine, as a huge structure supporting the entire wind turbine unit, need to be made of high-strength and high-rigidity metal materials to ensure that it stands stably on the ground and resists natural disasters such as strong winds and earthquakes. At the same time, metal components such as the nacelle and blade bracket need to have good aerodynamic performance and shock absorption capabilities to ensure that the wind turbine can efficiently and stably capture wind energy during operation. The manufacturing and maintenance of wind power metal components requires a high level of technology and strict quality control. Through precise design and fine manufacturing, these metal components can play a key role in wind power generation systems and provide humans with a steady supply of clean energy.
[0003] As an important part of the wind power generation system, wind power metal components are facing many challenges such as environmental corrosion resistance, wear resistance and deformation resistance. With the continuous development of wind power generation technology, the performance requirements for metal components are also increasing. On the one hand, environmental corrosion resistance is a major problem faced by wind power metal components. Since wind power stations are mostly built in harsh environments such as the seaside and desert, metal components are exposed to corrosive environments such as high humidity and high salinity for a long time, which are prone to rust and corrosion, seriously affecting their service life and safety. On the other hand, wear resistance is also a key point that needs to be improved for wind power metal components. During the operation of the wind turbine, the metal components will be eroded and worn by natural forces such as wind, sand and raindrops. If the wear resistance is insufficient, the surface of the components will be damaged, the performance will be reduced, and even failures will occur. Finally, deformation resistance is also an issue that needs to be focused on for wind power metal components. When the wind turbine is running, the metal components need to withstand complex wind loads and vibrations. If the deformation resistance is insufficient, the components will be deformed and fail, seriously affecting the stability and safety of the wind turbine.
[0004] Therefore, technical personnel in this field urgently need to study surface treatment methods that are resistant to environmental corrosion, wear, and deformation, in order to solve the failure problems of wind power metal components caused by environmental corrosion, wear, and deformation under complex working conditions. Summary of the invention
[0005] The purpose of the present invention is to provide an alloy film on the surface of a wind power metal component in view of the problems existing in the prior art. The alloy film has the characteristics of environmental corrosion resistance, wear resistance and deformation resistance.
[0006] At the same time, the present invention provides a method for treating alloy films on the surfaces of wind power metal components. The method prepares a metallurgical diffusion-bonded multilayer film with high hardness, strong wear resistance, environmental corrosion resistance, and not easy to peel off through the synergistic effects of ultrasonic shot peening, alternating sputtering, and segmented gradient heat treatment.
[0007] At the same time, the present invention provides an application of an alloy film on the surface of a wind power metal component in a wind power station in a harsh environment, wherein the harsh environment includes a seaside and a desert.
[0008] In order to solve the above technical problems, the technical solution adopted by the present invention is:
[0009] An alloy film on the surface of a wind power metal component comprises a multilayer structure of alternating TaNbW (tantalum niobium tungsten) layers and TiVCr (titanium vanadium chromium) layers metallurgically diffused and bonded on the surface of the wind power metal component.
[0010] Preferably, the wind turbine metal components include a wind turbine main shaft, a wind turbine bearing, a wind turbine tower, a wind turbine nacelle or a wind turbine blade bracket.
[0011] Preferably, the TaNbW layer and the TiVCr layer are of FCC (face-centered cubic) structure and grow on the (111) crystal plane.
[0012] Preferably, the single-layer thickness of the TaNbW layer and the TiVCr layer is 7.5-10 nm, and there are 60 layers each, and the total thickness of the obtained multilayer structure is 900-1200 nm.
[0013] A method for treating an alloy film on the surface of a wind power metal component comprises the following steps:
[0014] S1, surface cleaning: select the wind power metal components to be processed, clean the surface to remove stains, and then dry in the shade for later use;
[0015] S2, surface pretreatment: The wind power metal components cleaned by S1 are subjected to surface ultrasonic shot peening. During the shot peening process, the ultrasound is subjected to sine-cosine-sine alternating amplitude and frequency ultrasound with an amplitude of 25-35μm and a frequency of 20-30kHz. The first sine amplitude and frequency ultrasound is 1 / 4T, T is the total ultrasound time, the cosine amplitude and frequency ultrasound is 1 / 2T, and the last sine amplitude and frequency ultrasound is 1 / 4T;
[0016] S3, surface sputtering: The wind power metal components after ultrasonic shot peening on the surface of S2 are subjected to dual-target magnetron co-sputtering to prepare a multilayer structure of alternating TaNbW layers and TiVCr layers;
[0017] S4, segmented gradient heat treatment: place the wind power metal components after S3 surface treatment in a heating furnace plate, heat to 600~620℃ at 5~8℃ / min and keep warm for 1~1.5h, then cool to 450~480℃ at 3~5℃ / min and keep warm for 0.5~0.8h, then cool to 260~280℃ at 5~8℃ / min and keep warm for 0.8~1.2h, then cool to 120~130℃ at 10~15℃ / min, take out and place in the air for air cooling to room temperature.
[0018] Preferably, in S2, the ultrasonic shot peening process is as follows: the ultrasonic shot peening time is 1-1.5 h, the shot diameter is 2.5-3.5 mm, the shot peening distance is 12-16 mm, and the shot material is tungsten steel.
[0019] Preferably, in S3, the surface multilayer structure preparation process is: the working gas is pure argon, the flow rate is 25~30 sccm, the working gas pressure is 1.0~1.8 Pa, the bias voltage is -60~-55V, the target substrate distance is 55~60 mm, the sample disk rotation speed is 10~12 r / min, and the thin film is prepared by DC sputtering. Target 1 is a TaNbW target with a power of 100~150 W, a sputtering rate of 0.185~0.194 nm / s, and a sputtering time of 125~129 s; target 2 is a TiVCr target with a power of 100~150 W, a sputtering rate of 0.0684~0.0797 nm / s, and a sputtering time of 295~314 s, and sputtering is performed in an alternating sputtering manner.
[0020] Preferably, in S4, the heat treatment equipment is a built-in heating furnace plate of a magnetron co-sputtering equipment.
[0021] The alloy film on the surface of a wind power metal component obtained by the present invention has a Young's modulus greater than 328 GPa.
[0022] The invention discloses an alloy film on the surface of a wind power metal component for use in a wind power station in a harsh environment, wherein the harsh environment includes a seaside and a desert.
[0023] In the preparation process of the alloy film on the surface of a wind power metal component of the present invention, a three-step treatment of ultrasonic shot peening, alternating sputtering and segmented gradient heat treatment is performed on the surface of the wind power metal component, so that a TaNbW / TiVCr with a thickness of 900-1200 nm and an FCC structure grown along the (111) crystal direction and an alternating multilayer structure can be formed on the surface of the wind power metal component. The formation principle is as follows: The first step is to use a tungsten steel projectile with a diameter of 2.5~3.5mm to perform sine-cosine-sine alternating ultrasonic amplitude and frequency conversion at a distance of 12~16mm with an amplitude of 25~35μm and a frequency of 20~30kHz. The first sine amplitude and frequency conversion ultrasound is (1 / 4)T (T is the total ultrasonic time), the cosine amplitude and frequency conversion ultrasound is (1 / 2)T, and the last sine amplitude and frequency conversion ultrasound is (1 / 4)T. They are performed alternately. On the one hand, alternating gradual plastic deformation occurs on the surface of the wind power metal components, and a large number of deformation dislocations are caused to reciprocate in the process of ultrasonic shot peening, resulting in aggregation and intersection on the surface to form a large number of dislocation cells and grain boundaries. On the other hand, during the ultrasonic shot peening process, deformation internal stress gradually increases from the inside to the outside. Step 2: During the magnetron sputtering process, the thin film is prepared by DC sputtering with a pure argon flow rate of 25-30 sccm, a working gas pressure of 1.0-1.8 Pa, a bias voltage of -60-55V, a target-substrate distance of 55-60 mm, and a sample disk rotation speed of 10-12 r / min. Target 1 is a TaNbW target with a power of 100-150 W, a sputtering rate of 0.185-0.194 nm / s, and a sputtering time of 125-129 s; target 2 is a TiVCr target with a power of 100-150 W, a sputtering rate of 0.0684-0.0797 nm / s, and a sputtering time of 295-314 s preparation process, nucleation is formed at the dislocation cells and grain boundaries on the surface of the wind power metal component, and a TaNbW / TiVCr multilayer film with an alternating multilayer structure and a FCC structure growing along the (111) crystal direction with the lowest energy is formed under the action of gradient internal stress. The third step: During the segmented gradient heat treatment process, first heat to 600~620℃ at 5~8℃ / min and keep warm for 1~1.5h, then cool to 450~480℃ at 3~5℃ / min and keep warm for 0.5~0.8h, then cool to 260~280℃ at 5~8℃ / min and keep warm for 0.8~1.2h, then cool to 120~130℃ at 10~15℃ / min and take out and place in the air for air cooling to room temperature. Through the three-stage gradient heating, cooling and heat preservation heat treatment, on the one hand, through the insulation at a specific temperature, TaNbW / TiVCr continues to grow along the (111) crystal direction, which increases the strong texture characteristics of the film layer. On the other hand, the diffusion time of different alloy elements is guaranteed, so that metallurgical diffusion bonding occurs between layers and forms good bonding strength.
[0024] Compared with the prior art, the present invention has the following advantages:
[0025] 1. Environmental corrosion resistance: The TaNbW / TiVCr multilayer film formed by the present invention makes the surface of the wind power metal component resistant to environmental corrosion. The reasons are as follows: (1) TaNbW and TiVCr are both FCC structures, and their (111) crystal plane is an atomic close-packed plane. Compared with other structures, it has the characteristics of lowest energy, most stable structure and best corrosion resistance. (2) Thanks to the excellent corrosion resistance of TaNbW and TiVCr, the wind power metal components can effectively resist environmental corrosion during their service. (2) The unique structure of the TaNbW / TiVCr multilayer film enables the wind power metal components to form a multi-layer protective structure during their service, further enhancing their resistance to environmental corrosion.
[0026] 2. High hardness and strong wear resistance: The TaNbW / TiVCr multilayer film formed by the present invention makes the surface of the wind power metal component have high hardness and strong wear resistance. The reasons are as follows: (1) Thanks to the unique structure of the TaNbW / TiVCr multilayer film, both TaNbW and TiVCr have extremely high hardness and wear resistance, and can effectively resist wear during friction. (2) The TaNbW and TiVCr in the alloy film are FCC structures, composed of (111) crystal planes, forming a strong texture, which makes it have high hardness and strong wear resistance. (3) The TaNbW / TiVCr multilayer film and the substrate are annealed, and the contact surface undergoes metallurgical diffusion bonding to form a whole, which not only enhances the hardness of the surface, but also enables the wind power metal component to maintain stable performance under long-term and high-intensity friction environments.
[0027] 3. Excellent anti-deformation ability: TaNbW and TiVCr formed by the present invention are both FCC structures, and their (111) crystal plane is an atomic close-packed plane. The atomic density of the film layer grown along this direction is the highest, and the interaction force between atoms is the strongest, which causes the Young's modulus of the multilayer film to be significantly improved, and the overall anti-deformation ability of the wind power metal component is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0028] Figure 1 It is a microstructure diagram and composition test diagram of the alloy film of the present invention;
[0029] Figure 2 It is a component test diagram of the alloy film of the present invention. DETAILED DESCRIPTION
[0030] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments. The following embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention.
[0031] Example 1: In this example, an alloy film is prepared on the surface of a GCr15 wind turbine main shaft.
[0032] An alloy film on the surface of a wind power metal component comprises a multilayer structure of alternating TaNbW layers and TiVCr layers metallurgically diffused and bonded on the surface of a wind power main shaft.
[0033] The TaNbW layer and the TiVCr layer have an FCC structure and grow on the (111) crystal plane.
[0034] The single-layer film thickness of the TaNbW layer and the TiVCr layer is 7.5 nm, and there are 60 layers each. The total thickness of the obtained multilayer structure is 900 nm.
[0035] A method for treating an alloy film on the surface of a wind power metal component comprises the following steps:
[0036] S1, surface cleaning: select the wind turbine main shaft to be processed, clean its surface to remove stains, and then dry it in the shade for later use;
[0037] S2, surface pretreatment: the wind turbine main shaft cleaned by S1 is subjected to surface ultrasonic shot peening. During the shot peening process, the ultrasound is subjected to sine-cosine-sine alternating amplitude and frequency ultrasound with an amplitude of 25 μm and a frequency of 20 kHz. The first sine amplitude and frequency ultrasound is 1 / 4T, T is the total ultrasound time, the cosine amplitude and frequency ultrasound is 1 / 2T, and the last sine amplitude and frequency ultrasound is 1 / 4T.
[0038] S3, surface sputtering: The wind turbine main shaft after ultrasonic shot peening on the S2 surface is subjected to dual-target magnetron co-sputtering to prepare a multilayer structure of alternating TaNbW layers and TiVCr layers;
[0039] S4, segmented gradient heat treatment: place the wind turbine main shaft after S3 surface treatment in a heating furnace plate, heat to 600℃ at 5℃ / min and keep it for 1h, then cool to 450℃ at 3℃ / min and keep it for 0.5h, then cool to 260℃ at 5℃ / min and keep it for 0.8h, then cool to 120℃ at 10℃ / min, take out and place in the air for air cooling to room temperature.
[0040] In S2, the ultrasonic shot peening process is as follows: ultrasonic shot peening time is 1 h, shot diameter is 2.5 mm, shot peening distance is 12 mm, and the shot material is tungsten steel.
[0041] In S3, the preparation process of the surface multilayer structure is as follows: the working gas is pure argon with a flow rate of 25 sccm, a working gas pressure of 1.0 Pa, a bias voltage of -60 V, a target-substrate distance of 55 mm, and a sample disk rotation speed of 10 r / min. The film is prepared by DC sputtering. Target 1 is a TaNbW target with a power of 100 W, a sputtering rate of 0.185 nm / s, and a sputtering time of 125 s. Target 2 is a TiVCr target with a power of 100 W, a sputtering rate of 0.0684 nm / s, and a sputtering time of 295 s. Sputtering is performed in an alternating sputtering manner.
[0042] In S4, the heat treatment equipment is a built-in heating furnace plate of a magnetron co-sputtering equipment.
[0043] The Young's modulus of the alloy film on the surface of the wind turbine metal component and the alloy film on the surface of the wind turbine main shaft obtained in this embodiment is 328 GPa.
[0044] The alloy film on the surface of a wind power metal component of the present embodiment is used in a wind power station in a harsh environment, wherein the harsh environment includes a seaside and a desert.
[0045] like Figure 1 As shown, a strong texture is formed between the layers of the alloy film obtained in this embodiment, as well as between the alloy film and the substrate (i.e., the wind power metal component, i.e., the wind power main shaft), and metallurgical diffusion bonding occurs. The substrate and the alloy film, as well as the layers of the alloy film, form a whole, which not only enhances the surface hardness, but also enables the wind power main shaft to maintain stable performance under long-term and high-intensity friction environments.
[0046] like Figure 2 As shown, TaNbW and TiVCr in this embodiment are both FCC structures, and their (111) crystal plane is an atomic close-packed plane. Compared with other structures, it has the characteristics of lowest energy, most stable structure and best corrosion resistance.
[0047] Example 2: In this example, an alloy film is prepared on the surface of a 42CrMo4 wind turbine bearing.
[0048] An alloy film on the surface of a wind power metal component includes an alloy film metallurgically diffused and bonded on the surface of a wind power bearing. The alloy film is a multilayer structure formed by alternating TaNbW / TiVCr.
[0049] The TaNbW and TiVCr in the alloy film obtained on the surface have a FCC structure and grow on the (111) crystal plane.
[0050] The obtained TaNbW and TiVCr single-layer films have a thickness of 8.5 nm, and there are 60 layers each. The total thickness of the obtained multilayer film is 1020 nm.
[0051] A method for treating an alloy film on the surface of a wind power metal component comprises the following steps:
[0052] S1, surface cleaning: select the wind turbine bearings to be processed, clean their surfaces to remove stains, and then dry them in the shade for later use;
[0053] S2, surface pretreatment: The wind turbine bearings cleaned by S1 were subjected to surface ultrasonic shot peening. During the shot peening process, the ultrasound was performed with an amplitude of 30 μm and a frequency of 25 kHz for sine-cosine-sine alternating amplitude and frequency conversion ultrasound. The first sine amplitude and frequency conversion ultrasound was (1 / 4) T (T is the total ultrasonic time), the cosine amplitude and frequency conversion ultrasound was (1 / 2) T, and the last sine amplitude and frequency conversion ultrasound was (1 / 4) T.
[0054] The ultrasonic shot peening process is as follows: ultrasonic shot peening time T = 1.2h, shot diameter 3.0mm, shot peening distance 14mm, and shot material is tungsten steel;
[0055] S3, surface sputtering: The wind turbine bearing after ultrasonic shot peening on the surface of S2 is subjected to dual-target magnetron co-sputtering to prepare a multilayer structure of alternating TaNbW layers and TiVCr layers;
[0056] The preparation process of the surface multilayer structure is as follows: the working gas is pure argon gas, the flow rate is 28 sccm, the working gas pressure is 1.5Pa, the bias voltage is -58V, the target substrate distance is 58 mm, the sample disk rotation speed is 11 r / min, and the film is prepared by DC sputtering. Target 1 is TaNbW target, the power is 120 W, the sputtering rate is 0.190 nm / s, and the sputtering time is 127 s; target 2 is TiVCr target, the power is 130 W, the sputtering rate is 0.0750 nm / s, and the sputtering time is 305 s. The sputtering is done in an alternating sputtering manner.
[0057] S4, segmented gradient heat treatment: Place the wind turbine bearing after S3 surface treatment in a heating furnace plate, heat to 610℃ at 6.5℃ / min and keep it for 1.2h, then cool to 465℃ at 4℃ / min and keep it for 0.7h, then cool to 270℃ at 6℃ / min and keep it for 1.0h, then cool to 125℃ at 12℃ / min, take it out and place it in the air to cool to room temperature;
[0058] The heat treatment equipment is a magnetron co-sputtering equipment with a built-in heating furnace plate.
[0059] The alloy film on the surface of a wind power metal component of the present embodiment is used in a wind power station in a harsh environment, wherein the harsh environment includes a seaside and a desert.
[0060] Example 3: In this example, an alloy film is prepared on the surface of a Q345E wind turbine tower.
[0061] An alloy film on the surface of a wind power metal component includes an alloy film metallurgically diffused and bonded on the surface of a wind power tower, wherein the alloy film is a multilayer structure formed by alternating TaNbW / TiVCr.
[0062] The TaNbW and TiVCr in the alloy film obtained on the surface have a FCC structure and grow on the (111) crystal plane.
[0063] The obtained TaNbW and TiVCr single-layer films have a thickness of 10 nm, and there are 60 layers each. The total thickness of the obtained multilayer film is 1200 nm.
[0064] A method for treating an alloy film on the surface of a wind power metal component comprises the following steps:
[0065] S1, surface cleaning: select the wind turbine tower to be treated, clean its surface to remove stains, and then dry it in the shade for later use;
[0066] S2, surface pretreatment: The wind turbine tower cleaned by S1 is subjected to surface ultrasonic shot peening. During the shot peening process, the ultrasound is subjected to sine-cosine-sine alternating amplitude and frequency ultrasound with an amplitude of 35μm and a frequency of 30kHz. The first sine amplitude and frequency ultrasound is (1 / 4)T (T is the total ultrasound time), the cosine amplitude and frequency ultrasound is (1 / 2)T, and the last sine amplitude and frequency ultrasound is (1 / 4)T.
[0067] The ultrasonic shot peening process is as follows: the ultrasonic shot peening time T is 1.5h, the shot diameter is 3.5mm, the shot peening distance is 16mm, and the shot material is tungsten steel;
[0068] S3, surface sputtering: The wind power metal components after ultrasonic shot peening on the surface of S2 are subjected to dual-target magnetron co-sputtering to prepare a multilayer structure of alternating TaNbW layers and TiVCr layers;
[0069] The preparation process of the surface multilayer structure is as follows: the working gas is pure argon gas, the flow rate is 30 sccm, the working pressure is 1.8Pa, the bias voltage is -55V, the target substrate distance is 60mm, the sample disk rotation speed is 12 r / min, and the film is prepared by DC sputtering. Target 1 is TaNbW target, the power is 150 W, the sputtering rate is 0.194 nm / s, and the sputtering time is 129 s; target 2 is TiVCr target, the power is 150 W, the sputtering rate is 0.0797 nm / s, and the sputtering time is 314 s. The sputtering is done in an alternating sputtering manner.
[0070] S4, segmented gradient heat treatment: place the wind power metal component after S3 surface treatment in a heating furnace plate, heat to 620℃ at 8℃ / min and keep it for 1.5h, then cool to 480℃ at 5℃ / min and keep it for 0.8h, then cool to 280℃ at 8℃ / min and keep it for 1.2h, then cool to 130℃ at 15℃ / min, take it out and place it in the air to cool to room temperature;
[0071] The heat treatment equipment is a magnetron co-sputtering equipment with a built-in heating furnace plate.
[0072] The alloy film on the surface of a wind power metal component of the present embodiment is used in a wind power station in a harsh environment, wherein the harsh environment includes a seaside and a desert.
[0073] Comparative Example 1: This comparative example differs from Example 1 only in that ultrasonic shot peening was not performed.
[0074] Comparative Example 2: The only difference between this comparative example and Example 1 is that no segmented gradient heat treatment is performed. Specifically, the heat treatment process of this comparative example is: the wind turbine main shaft after S3 surface treatment is placed in a heating furnace plate, heated to 600°C at 5°C / min and kept warm for 2h, then cooled to 120°C at 10°C / min, taken out and placed in the air for air cooling to room temperature.
[0075] Comparative Example 3: The difference between this comparative example and Example 1 is that the ultrasonic shot peening treatment is performed with an amplitude of 25 μm and a frequency of 20 kHz.
[0076] Comparative Example 4: The only difference between this comparative example and Example 1 is that in the ultrasonic shot peening process, the ultrasound is subjected to sine-cosine alternating amplitude and frequency conversion ultrasound with an amplitude of 25 μm and a frequency of 20 kHz, wherein the sine amplitude and frequency conversion ultrasound is 1 / 2T, where T is the total ultrasonic time, and the cosine amplitude and frequency conversion ultrasound is 1 / 2T.
[0077] The performance parameters of the alloy films obtained in Examples 1 to 3 of the present invention are shown in Table 1 below.
[0078] Table 1 Performance parameters of Examples 1 to 3
[0079]
[0080] The performance parameters of the alloy film obtained in the comparative example of the present invention are shown in Table 2 below.
[0081] Table 2 Comparative performance parameters
[0082]
[0083] It should be understood that in order to streamline the present disclosure and aid in understanding one or more of the various inventive aspects, in the above description of exemplary embodiments of the present invention, various features of the present invention are sometimes grouped together into a single embodiment, figure, or description thereof. However, this disclosed method should not be interpreted as reflecting the intention that the claimed invention requires more features than those expressly recited in each claim. Rather, as reflected in the claims, inventive aspects lie in less than all of the features of the previously disclosed embodiments. Therefore, the claims that follow the detailed description are hereby expressly incorporated into the detailed description, with each claim itself serving as a separate embodiment of the present invention.
[0084] Although the present invention has been described according to a limited number of embodiments, it will be apparent to those skilled in the art, with the benefit of the above description, that other embodiments may be envisioned within the scope of the invention thus described. In addition, it should be noted that the language used in this specification is selected primarily for readability and teaching purposes, rather than for explaining or defining the subject matter of the present invention. Therefore, many modifications and variations will be apparent to those skilled in the art without departing from the scope and spirit of the appended claims. The disclosure of the present invention is illustrative, not restrictive, with respect to the scope of the present invention, which is defined by the appended claims.
[0085] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for treating an alloy film on the surface of a wind power metal component, characterized in that: The following steps are involved: S1, surface cleaning: select the wind power metal components to be processed, clean the surface to remove stains, and then dry in the shade for later use; S2, surface pretreatment: The wind power metal components cleaned by S1 are subjected to surface ultrasonic shot peening. During the shot peening process, the ultrasound is subjected to sine-cosine-sine alternating amplitude and frequency ultrasound with an amplitude of 25-35μm and a frequency of 20-30kHz. The first sine amplitude and frequency ultrasound is 1 / 4T, T is the total ultrasound time, the cosine amplitude and frequency ultrasound is 1 / 2T, and the last sine amplitude and frequency ultrasound is 1 / 4T; S3, surface sputtering: The wind power metal components after ultrasonic shot peening on the surface of S2 are subjected to dual-target magnetron co-sputtering to prepare a multilayer structure of alternating TaNbW layers and TiVCr layers; S4, segmented gradient heat treatment: place the wind power metal component after S3 surface treatment in a heating furnace plate, heat to 600~620℃ at 5~8℃ / min and keep warm for 1~1.5h, then cool to 450~480℃ at 3~5℃ / min and keep warm for 0.5~0.8h, then cool to 260~280℃ at 5~8℃ / min and keep warm for 0.8~1.2h, then cool to 120~130℃ at 10~15℃ / min, take out and place in the air for air cooling to room temperature; The TaNbW layer and TiVCr layer have FCC structure and grow on (111) crystal plane; The single-layer thickness of the TaNbW layer and the TiVCr layer is 7.5~10nm, and there are 60 layers each. The total thickness of the obtained multilayer structure is 900~1200nm.
2. The processing method according to claim 1, characterized in that: In S2, the ultrasonic shot peening process is as follows: ultrasonic shot peening time is 1~1.5h, shot diameter is 2.5~3.5mm, shot peening distance is 12~16mm, and the shot material is tungsten steel.
3. The processing method according to claim 1, characterized in that: In S3, the preparation process of the surface multilayer structure is as follows: the working gas is pure argon with a flow rate of 25~30 sccm, a working gas pressure of 1.0~1.8 Pa, a bias voltage of -60~-55V, a target-substrate distance of 55~60 mm, a sample disk rotation speed of 10~12 r / min, and a DC sputtering method is used to prepare the thin film. Target 1 is a TaNbW target with a power of 100~150 W, a sputtering rate of 0.185~0.194 nm / s, and a sputtering time of 125~129 s; target 2 is a TiVCr target with a power of 100~150 W, a sputtering rate of 0.0684~0.0797 nm / s, and a sputtering time of 295~314 s. Sputtering is performed in an alternating sputtering manner.
4. The processing method according to claim 1, characterized in that: In S4, the heat treatment equipment is a built-in heating furnace plate of a magnetron co-sputtering equipment.
5. The alloy film on the surface of a wind power metal component obtained by the treatment method according to any one of claims 1 to 4, characterized in that: The invention comprises a multilayer structure of alternating TaNbW layers and TiVCr layers metallurgically diffused and bonded on the surface of a wind power metal component.
6. The alloy film on the surface of a wind power metal component according to claim 5, characterized in that: The Young's modulus of the alloy film on the surface of wind power metal components is greater than 328GPa.
7. The alloy film on the surface of a wind power metal component according to claim 5, characterized in that: Wind power metal components include wind power main shaft, wind power bearings, wind power tower, wind power nacelle or wind power blade bracket.
8. The use of the alloy film on the surface of a wind power metal component according to claim 5 in a wind power station in a harsh environment, characterized in that: Harsh environments include seaside and desert.
Citation Information
Patent Citations
Method for preparing ceramic multilayer film on metal surface by chemical heat treatment
CN113621937A
Multi-element laminated structure hard coating and preparation method thereof
CN115679249A